Informational and methodological support for graphical training of future engineers - Shkitsa, L.; Kornuta, O. (Problems of Engineer-Pedagogical Education, 2018)
Enhancement of graphical competency of future engineers is an important task for the development of an innovative personality type in the context of the conceptual modernization of the national education. The article substantiates the content of educational and methodological support for graphic disciplines in accordance with the changes that are taking place in the system of technical engineering. The experience of teaching engineering graphics, which contributes to the improvement of traditional teaching methods through the system of familiarization with the current State Standards and ISO Standards and wide application of the three-dimensional modeling in the educational process, is offered. Graphic profession-oriented activity is carried out while using the training system for the design of drilling equipment, which acquaints users with existing general requirements and normative regulations for preparing various engineering documents and allows choosing typical equipment and necessary information for its design and engineering.